1982
DOI: 10.1182/blood.v59.5.1036.bloodjournal5951036
|View full text |Cite
|
Sign up to set email alerts
|

Murine monoclonal antibody therapy in two patients with chronic lymphocytic leukemia

Abstract: We infused the murine monoclonal antibody T101 into two patients with advanced refractory chronic lymphocytic leukemia (CLL) after confirming its reactivity with their CLL cells. One patient received doses of 1, 3, and 12 mg; the second patient received 10 mg. Antibody was delivered over 10--15 min. The major observations were: (1) T101 murine monoclonal antibody did bind to cells with T65 surface antigen and saturated these cells in vivo; (2) cells that bound T101 disappeared from the circulation by 2 hr afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This has been observed in patients treated doubling time of 18 hr in vitro (de Both et al, 1981) on day 5 , with xenogeneic mouse MAbs, leading to reduction of therayields a maximum of 9.7 x lo8 RMB-1 cells. This would peutic efficacy (Miller et al, 1983) or to hypersensitivity imply that cures can be achieved in animals containing a reactions (Dillman et al, 1982). The use of syngeneic MAbs number of tumor cells that is approx.…”
Section: Discussionmentioning
confidence: 99%
“…This has been observed in patients treated doubling time of 18 hr in vitro (de Both et al, 1981) on day 5 , with xenogeneic mouse MAbs, leading to reduction of therayields a maximum of 9.7 x lo8 RMB-1 cells. This would peutic efficacy (Miller et al, 1983) or to hypersensitivity imply that cures can be achieved in animals containing a reactions (Dillman et al, 1982). The use of syngeneic MAbs number of tumor cells that is approx.…”
Section: Discussionmentioning
confidence: 99%
“…The use of monoclonal antibodies has not been restricted to the analysis of cellular function. Clinical trials are underway to explore the effects of monoclonal antibodies as therapeutic tools for the treatment of malignant and immunoregulatory diseases (11)(12)(13)(14)(15)34). We have found that circulating Leu-1 antigen can be detected in the serum of patients after monoclonai antibody infusion (11).…”
Section: Discussionmentioning
confidence: 99%